Dynamic pH barrage junction focusing of amino acids, peptides, and digested monoclonal antibodies in capillary electrophoresis–mass spectrometry. Issue 21 (3rd June 2020) - Wang, Lingyu; Cheng, Jianhui; McNutt, Julie E.; Morin, Gregg B.; Chen, David D. Y.
Abstract: Dynamic pH barrage junction focusing in CE enables effective signal enhancement, quantitative capture efficiencies, and straightforward optimization. The method is a technical variant of dynamic pH junction focusing. CE separation with dynamic pH barrage junction focusing is compatible with both optical and mass spectrometric detection. We developed a CE–MS/MS method using hydrophilic polyethyleneimine‐coated capillaries and validated it for the qualitative analysis of amino acids, peptides, and tryptic peptides of digested monoclonal antibodies. The S/N of extracted ion electropherograms of zwitterionic analytes were enhanced by approximately two orders of magnitude with a tradeoff of a shortened separation window. Online focusing improved the MS signal intensity of a diluted antibody digest, enabling more precursor ions to be analyzed with subsequent tandem mass spectrometric identification. It also broadened the concentration range of protein digest samples for which adequate sequence coverage data can be obtained. With only 0.9 ng of digested infliximab sample loaded into the capillary, 76% and 100% sequence coverage was realized for antibody heavy and light chains, respectively, after online focusing. Full coverage was achieved with 9 ng of injected digest.